Promoting solutions and co-constructing problems – management consultancy and instrument constituencies. Issue 1 (8th September 2017) - Sturdy, Andrew
Abstract: The concept of 'instrument constituencies' has recently emerged in policy research to reflect actors and practices focused primarily on articulating and promoting policy solutions. A central component of this is that, with such an emphasis on promotion, policy-maker decisions are subject to supply push rather than being demand-led. In particular, the 'solutions' of instrument constituencies come before, rather than after, the problems they are held to solve – solutions chasing problems. Key actors here are external consultants. However, the extent to which their activities match the problem chasing of the instrument constituency concept is untested. As a start in addressing such neglect, this article draws on data from secondary sources from research, outside the policy field, in organisation studies. In particular, it compares promotional practices in consulting with the supply push element of the instrument constituency model, finding that they correspond, but only partially. Consultants do not always construct problems for their clients to fit their prepared solutions, nor do they simply conform to the conventional, 'rational' model. Rather, it is shown that they also simultaneously co-produce both problems and solutions with clients, combining supply-push and demand-led approaches. Thus, it is argued that the model need not be so strongly associated with problem chasing (and non-rational decisions). Rather, the case of consultancy draws attention to how decision-making through instrument constituencies can occur along a continuum of three positions, from problems pre-dating solutions, being (co-) constructed at the same time, to their production after the 'solution'.